Export Diversification in Economic Communities of Central African Countries: The Role of Infrastructure - NGASSAM, Sylvain Bertelet; Ngameni, Joseph Pasky; Tiwang, Gildas Ngueuleweu; Kemmanang, Ludovic Feulefack (Asian Journal of Economic Modelling, 2022)
Conscious of the low infrastructure development in Economic Community of Central African States (ECCAS), governments have invested important financial resources aimed at increasing the global stock of infrastructure, which indexes have raised from 11.13 in 2000 to 16.65 in 2018. In the same period, the average export concentration index slightly decreased from 4.92 in 2000 to 4.90 in 2014. Given the disproportionate improvement of infrastructure and export diversification, the study objective is to examine the effects of infrastructure on export diversification in ECCAS over the 2000–2016 period. Overall export diversification, and export diversification at extensive and intensive margins, are used as indicators. The fully modified ordinary least squares (FMOLS) and the dynamic ordinary least squares (DOLS) estimators are used for semi-parametric instrumental variable estimates that correct for serial correlation and endogeneity problems. The empirical results indicate that electricity and mobile phone infrastructure positively contribute to the overall and the export diversification along intensive margin, while transport infrastructure and internet negatively contribute to export diversification. The policy implications are that the stock of infrastructure should be increased quantitatively and qualitatively. The spatial distribution of infrastructure must depend on their capacity to produce a variety of tradable goods and services. The export diversification policies in ECCAS will prioritize infrastructure and the development of new export categories. Investment in infrastructure may be accompanied by trade and investment liberalization and by financial development.